Numerical calibration of an easy method for seismic behaviour assessment on large scale of masonry building aggregates. (February 2015) - Formisano, Antonio; Florio, Gilda; Landolfo, Raffaele; Mazzolani, Federico M.
Abstract: The paper deals with the numerical calibration of a speedy procedure for large scale seismic vulnerability assessment of masonry building aggregates, which are typical building compounds diffused within historical centres of many Italian towns. First of all, based on several numerical analyses developed with the 3MURI calculation program, this simplified assessment procedure has been implemented, it being derived from the well known vulnerability form for masonry buildings integrated by five parameters accounting for the aggregate conditions among adjacent units. Later on, the set-up procedure has been validated through an application to a single building aggregate in the Vesuvius area. Since the results previously achieved have been again confirmed, subsequently the procedure has been used to investigate a wide area of the historical centre of Torre del Greco, allowing for the knowledge of the buildings most at risk under earthquake. Finally, the methodology has been applied to the historical centre of Poggio Picenze (AQ), damaged by the recent Italian earthquake (2009), in order to prove its effectiveness to foresee the damage level experienced by other types of masonry aggregates under seismic actions.